Quo Vadis Indonesian Labor Act: How Far the Protection for Labors? - Kukuh Pambudi (Journal of Law and Legal Reform, 2021)
Basic human rights for Indonesian workers are set out in constitution both in the 1945 Constitution, Law Number 39 Year 1999 regarding Human Rights, as well as in Law Number 13 of 2003 on Employment. Although there are regulations that regulate human rights for the people labor, but in fact many violations occur. Proven with the existence of Article 64 of the Manpower Act regulating Outsourcing, where in its development with the outsourcing system there are many shifts in the application of outsourcing system. Outsourcing is initially only imposed on that type of work not directly related to the production process of that activity relating outside the core business of a company, will but in reality almost all types of jobs are subject to outsourcing This research will describe in relation to the protection of human rights for the workforce especially for outsoutcing in labor Indonesia. The research method used is normative Juridical with the approach used is the Legislation Approach. The results obtained that with the Decision of the Constitutional Court Number 27 / PUU-IX / 2011 concerning Request for Testing of Law Number 13 of 2003 on Employment of the 1945 Constitution, is one form of legal protection for outsourced workers. Because in the verdict states that outsourcing only is permitted for the types of work listed in Article 59 of the Manpower Law.